A Literature Review on the Use of Interactive Mind Maps with Mentoring to Improve Science Learning Outcomes in Elementary Schools - Hidayati, Festi; Waluyo, Edi; Widiarti, Nuni; Yuwono, Agus (Indonesian Journal of Instructional Media and Model, 2025)
Improving learning outcomes in Natural and Social Sciences (IPAS) at the elementary school level remains a challenge, particularly in fostering students’ conceptual understanding and critical thinking skills. Conventional instructional approaches often fail to optimally support these competencies, indicating the need for innovative learning strategies. This study aims to analyze the effectiveness of mentoring-based interactive mind map media in enhancing elementary school students’ IPAS learning outcomes. A literature review method was employed by examining 241 articles retrieved from Google Scholar and Publish or Perish databases. Through an inclusion and exclusion process, 25 relevant national and international articles published between 2020 and 2025 were selected for analysis. The findings reveal that the integration of interactive mind maps with mentoring consistently contributes to improved learning outcomes, student engagement, conceptual clarity, and critical thinking abilities. The effectiveness of this approach is strongly influenced by systematic instructional planning and teachers’ readiness to function as mentors. In conclusion, mentoring-based interactive mind map media represent a promising and innovative instructional alternative for IPAS learning in elementary schools. This study contributes theoretically by synthesizing evidence on integrated visual and mentoring-based learning, and practically by providing insights for educators in designing more effective IPAS instruction.